Homo sapiens Is as Homo sapiens Was : behavioral variability versus "behavioral modernity" in paleolithic archaeology - Shea, John J. (University of Chicago, 2011)
Paleolithic archaeologists conceptualize the uniqueness of Homo sapiens in terms of Òbehavioral modernity,Ó a quality often conflated with behavioral variability. The former is qualitative, essentialist, and a historical artifact of the European origins of Paleolithic research. The latter is a quantitative, statistically variable property of all human behavior, not just that of Ice Age Europeans. As an analytical construct, behavioral modernity is deeply flawed at all epistemological levels. This paper outlines the shortcomings of behavioral modernity and instead proposes a research agenda focused on the strategic sources of human behavioral variability. Using data from later Middle Pleistocene archaeological sites in East Africa, this paper tests and falsifies the core assumption of the behavioral-modernity conceptÑthe belief that there were significant differences in behavioral variability between the oldest H. sapiens and populations younger than 50 kya. It concludes that behavioral modernity and allied concepts have no further value to human origins research. Research focused on the strategic underpinnings of human behavioral variability will move Paleolithic archaeology closer to a more productive integration with other behavioral sciences.